The effect of earning information, cash flow components, and financing decision on stock returns: empirical evidence on Indonesia stock exchange - Mia Kasmiati; Perdana Wahyu Santosa (Universitas Hayam Wuruk Perbanas, 2019)
Trading, Service, and Investment sectors show an essential role in the national economy, and they have grown significantly during the past years. They have created many job opportunities in both the formal sector and the non-formal sector. This study aims to analyze the effect of net profit, operating cash flow, financing cash flow and investing cash flow and, financing decisions on stock’s return of service industry listed at Indonesia Stock Exchange (IDX). The analysis was done using the data panel regression. It shows that earning information, operating cash flow, financing cash flow positively affect stock returns. However, investing cash flow and financing decisions (proxy leverage) show a negative effect on the stock's return significantly. Simultaneously, the variables above affect stock return significantly. The implication is that management should pay more attention to financial factors, especially net profit, cash flow, and leverage to increase stock return and the company’s value.